Comparison of the mechanical properties of different skin sites for auricular and nasal reconstruction - M. F. Griffin; B. C. Leung; Y. Premakumar; M. Szarko; P. E. Butler (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Autologous and synthetic nasal and auricular frameworks require skin coverage. The surgeon’s decides on the appropriate skin coverage for reconstruction based on colour matching, subcutaneous tissue thickness, expertise and experience. One of the major complications of placing subcutaneous implants is the risk of extrusion (migration through the skin) and infection. However, knowledge of lessening the differential between the soft tissue and the framework can have important implications for extrusion. This study compared the mechanical properties of the skin commonly used as skin sites for the coverage in auricular and nasal reconstruction. Methods Using ten fresh human cadavers, the tensile Young’s Modulus of the skin from the forehead, forearm, temporoparietal, post-auricular and submandibular neck was assessed. The relaxation rate and absolute relaxation level was also assessed after 90 min of relaxation. Results The submandibular skin showed the greatest Young’s elastic modulus in tension of all regions (1.28 MPa ±0.06) and forearm showed the lowest (1.03 MPa ±0.06). The forehead demonstrated greater relaxation rates among the different skin regions (7.8 MPa−07 ± 0.1). The forearm showed the lowest rate of relaxation (4.74 MPa−07 ± 0.1). The forearm (0.04 MPa ±0.004) and submandibular neck skin (0.04 MPa ±0.005) showed similar absolute levels of relaxation, which were significantly greater than the other skin regions (p < 0.05). Conclusions This study provides an understanding into the biomechanical properties of the skin of different sites allowing surgeons to consider this parameter when trying to identify the optimal skin coverage in nasal and auricular reconstruction.